The Influence of Principal Leadership and Work Motivation on Teaching Quality of Teachers in Ogan Komering Ulu Timur (OKUT) Vocational School - Mensissusanto Mensissusanto; Bukman Lian; Alhadi Yan Putra (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
This study aims to determine the influence of principal leadership and work motivation on teaching quality of teachers in  Ogan Komering Ulu Timur  (OKUT) vocational school. The formulation of the problem in this study: (1) is there an influence of the principal leadership on the quality of teacher teaching?, (2) is there an influence of teacher work motivation on teaching quality?, (3) is there an influence between principal leadership and work motivation on teaching quality of teacher in OKUT vocational school. This study uses a quantitative descriptive method to see the effect partially between the existing variables. The results of this study obtained respondents' perceptions of the principal leadership obtained a score range of 116-150 and an average score of 130.79. Respondents' perceptions of performance motivation on teaching quality of teacher were obtained scores of 107-151 with a total score of 20191.00 and an average score of 134.43. The degree of influence of the principal leadership variable (X1) and the work motivation variable (X2) on teacher's teaching quality (Y) was 0.73 or 73%. Shows that teaching quality of teacher (Y) is jointly (simultaneously) influenced by the principal leadership variable (X1) and work motivation variable (X2) by 73% while the remaining 27% is influenced by other factors outside the equation model.